Legal Regulation of the Principles of State Activity in Family Relations - Nalyvaiko, Larysa; Obushenko, Nataliia; Boikov, Vladyslav; Hryshyna, Natalia; Makhova , Liliia (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
This work examines some challenges in the application of the principles of family law. It is found that the principles of family law cannot replace the legal norms that regulate family relations. However, the regulatory influence of family law norms is determined and limited by its principles. It is proven that the principles of family law can be applied by authorized law-making bodies (in the process of law-making), administrative, judicial bodies, and subjects of family relations (in the process of law enforcement). It is established that the legality of the actions of public institutions and private individuals directly depends on compliance with the principles of family law. It is substantiated that the principles of family law are implemented in the process of law-making, implemented through the norms of law, and in the process of direct application. In the process of law-making, the principles of family law establish requirements for law-making activity that cannot contradict general values. They determine the content of legal norms that must reflect these values and serve as a criterion for the conformity of family law norms with the law. It has been established that the application of family law principles is possible by embedding them in family law norms. At the same time, the principles of family law are not limited to the list that can be fixed in written law. It has been proven that consolidating family law principles in written law contributes to their practical implementation. The features of applying family law principles through legal analogy have been studied. It has been established that the analogy guarantees participants in family relations that their rights and obligations will be regulated, allowing them to resolve cases within the framework of family legislation or based on the principles of family law. REFERENCES: Decision of the Tyachiv District Court of the Transcarpathian region dated May 15, 2019, in case No. 307/1041/19. http://www.reyestr.court.gov.ua/Review/81775605 General theory of law: textbook / ed. by M.I. Kozyubry. Kyiv, 2015. 392 p. Halaburda, Nadiia. Leheza, Yevhen, Chalavan, Viktor. Yefimov, Volodymyr. Yefimova, Inna. 2021. Compliance with the principle of the rule of law guarantees the legality of providing public services in Ukraine. Journal of law and political sciences. Vol. 29, Іssue 4, 100–121. Kobrusieva, Yevheniiа. Leheza, Yevhen. Rudoi, Kateryna. Shamara, Oleksandr. Chalavan, Viktor. 2021. International standards of social protection of internally displaced persons: administrative and criminal aspects. Journal Cita Hukum Indonesian Law Journal. Vol. 9, No. 3, 461–484. DOI: https://doi.org/10.15408/jch.v9i3.23752 Kostruba A.V. Analogy of law and law as a factual fiction and a way to